Profile Matching for Web-Based Job Placement at SMKN 2 Tangerang - Irwan Febry Armansyah; Irwanto Irwanto; Moh. Fawaid; Siswo Wardoyo; Suhendar Suhendar; Leandro Costa (Technomedia Journal, 2026)
The Special Job Exchange, or Bursa Kerja Khusus (BKK), is a school-based career service unit that supports graduate placement and strengthens the link between vocational education and industry needs. However, BKK services at SMKN 2 Tangerang were still managed conventionally through manual alumni records, simple spreadsheets, and informal job vacancy dissemination. This study developed a web-based BKK information system integrated with the Profile Matching method to support alumni data management, job vacancy distribution, and competency-based job recommendation. The study used a Research and Development approach with the Waterfall model, including requirement analysis, system design, implementation, testing, and maintenance. The system was developed using PHP and MySQL. The results showed that the system supported centralized alumni data management, real-time vacancy information distribution, and structured job recommendation ranking. Black Box Testing indicated that all main features functioned according to user requirements, while algorithmic verification confirmed that the Profile Matching calculation was consistent with manual computation. User Acceptance Testing produced an average score of 91%, indicating that the system was feasible for supporting digital BKK services.